2009
DOI: 10.3855/jidc.419
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Resistance to nalidixic acid in Salmonella enterica serovar Typhi in Central India

Abstract: Background: Fluoroquinolones are the drugs of choice for the treatment of typhoid fever. But the recent increase in minimum inhibitory concentration (MIC) values of ciprofloxacin in Salmonella Typhi may result in delayed response and serious complications. Nalidixic acid resistance has been used as an indirect evidence of increased minimum inhibitory concentration for ciprofloxacin in Salmonella Typhi. Methods: We evaluated the isolates received at the National Salmonella and Escherichia Centre for nalidixic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
6
16
0
2
Order By: Relevance
“…So antibiotics must be used very judiciously to lower the development of multidrug resistance Salmonella serotpyes.) Antibiotic sensitivity pattern in present study correlates with the observation of Kumar et al, 22 who reported Ciprofloxacin sensitive Salmonella isolates. The results in present study are at par with the results reported by Chao et al, 23 who reported increased resistance of Salmonella Typhimurium strains to Doxycycline, Colistin, Sulfamethoxazole-trimethoprim and Cephalothin.…”
Section: Discussionsupporting
confidence: 91%
“…So antibiotics must be used very judiciously to lower the development of multidrug resistance Salmonella serotpyes.) Antibiotic sensitivity pattern in present study correlates with the observation of Kumar et al, 22 who reported Ciprofloxacin sensitive Salmonella isolates. The results in present study are at par with the results reported by Chao et al, 23 who reported increased resistance of Salmonella Typhimurium strains to Doxycycline, Colistin, Sulfamethoxazole-trimethoprim and Cephalothin.…”
Section: Discussionsupporting
confidence: 91%
“…Variable isolation rate of NAR strains from 2.3% to 96% has been documented. 3,17 Similar findings have been reported from neighbouring regions as Pakistan, Bangladesh, Nepal and other countries. 9,[18][19][20] In the present study high isolation rate of NARST 97.5% in comparison to earlier studies was seen.…”
Section: -15supporting
confidence: 77%
“…3,16 Nalidixic acid resistance is a surrogate marker to detect decreased ciprofloxacin susceptibility. Variable isolation rate of NAR strains from 2.3% to 96% has been documented.…”
Section: -15mentioning
confidence: 99%
“…In the present scenario of fluoroquinolone resistance and the increasing number of reports on the re-emergence of susceptibility to old drugs in the central west part of India, the findings presented here may be of immense importance to aid health authorities to rationalize the policy of empirical treatment of typhoid fever. Furthermore, the return to the use of these drugs includes advantages such as their availability in the developing world, their lower cost and their wellestablished clinical efficacy [36]. It should be noted that the risk of relapse and the development of a carrier state have been found to be higher among patients treated with ampicillin than those treated with chloramphenicol [37,38].…”
Section: Discussionmentioning
confidence: 99%